Does Good Corporate Governance contribute to Tax Aggressiveness in the Banking Sector - Novitasari, Sofia; Aldian Idrayahya, Esa; Wahyuningtiyas, Dicka; Anjelita, Shera; Amrulloh, Amri (Journal Economic Business Innovation, 2024)
This study aims to determine how much influence good corporate governance is measured by the gender of the board of commissioners, the quality of external auditors and institutional ownership on tax aggressiveness. This research was conducted on banking companies listed on the Indonesia Stock Exchange in 2020-2022. This study used quantitative methods with purposive sampling techniques with a total sample number of 69. The analysis methods used in this study are classical assumption test and multiple linear regression analysis with SPSS Statistics 22 tool. The results of this study show that the gender of the board of commissioners, the quality of external auditors and institutional ownership do not affect tax aggressiveness. The limitations of this study include limited independent variables, auditor quality measurement is not optimal, supporting theory references are limited, and many companies do not provide complete information, so the research sample is reduced. Researchers suggest adding independent variables, avoiding dummy variables in measuring the quality of external auditors, as well as increasing the research period for stronger analysis.